2019
DOI: 10.4274/balkanmedj.galenos.2019.2019.8.40
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma histone H4 levels are an important risk factor for the development of septic cardiomyopathy

Abstract: Background: Myocardial impairment is a major complication and an important prognostic predictor of sepsis. Therefore, early and accurate diagnosis as well as timely management of septic cardiomyopathy is critical to achieve favorable outcomes. Aims: To investigate the risk factors of septic cardiomyopathy. Study Design: Cross-sectional study Methods: This study performed between May 2016 and June 2018 recruited 93 septic patients from the intensive care unit. All patients received standardized treatments. Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…However, since there exists no significant myocardial injury in patients with TTC, plasma histone H4 levels might be expected to be much lower in TTC patients in comparison to patients with S-CMP, even if this S-CMP is of a fully reversible nature. Accordingly, comparison of S-CMP cases with global and segmental wall motion abnormalities with regard to admission rates, as well as plasma histone H4 levels, might have been an interesting subgroup analysis in the study (1). Within this context, patients with segmental wall motion abnormalities on TTE, together with relatively lower histone H4 levels, might strongly suggest an existing TTC rather than S-CMP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, since there exists no significant myocardial injury in patients with TTC, plasma histone H4 levels might be expected to be much lower in TTC patients in comparison to patients with S-CMP, even if this S-CMP is of a fully reversible nature. Accordingly, comparison of S-CMP cases with global and segmental wall motion abnormalities with regard to admission rates, as well as plasma histone H4 levels, might have been an interesting subgroup analysis in the study (1). Within this context, patients with segmental wall motion abnormalities on TTE, together with relatively lower histone H4 levels, might strongly suggest an existing TTC rather than S-CMP.…”
mentioning
confidence: 99%
“…In clinical practice, septic cardiomyopathy (S-CMP) has been regarded as a poorly understood phenomenon with a variety of underlying mechanisms-including detrimental impacts of cytokines and nitric oxide on the myocardium-and generally presents with emerging systolic and/or diastolic dysfunction on transthoracic echocardiogram (TTE) in septic patients (1)(2)(3). Within this context, the association of inflammation markers, in particular, with left ventricular systolic dysfunction might also be substantiated by previous reports in diverse clinical scenarios other than sepsis (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
In clinical practice, septic cardiomyopathy (S-CMP) has been regarded as a poorly understood phenomenon with a variety of underlying mechanisms-including detrimental impacts of cytokines and nitric oxide on the myocardium-and generally presents with emerging systolic and/or diastolic dysfunction on transthoracic echocardiogram (TTE) in septic patients (1)(2)(3). Within this context, the association of inflammation markers, in particular, with left ventricular systolic dysfunction might also be substantiated by previous reports in diverse clinical scenarios other than sepsis (4).
…”
mentioning
confidence: 99%
“…Interestingly, S-CMP, though renowned for its reversible nature (1), might not fully recover in certain settings, potentially suggesting some degree of permanent myocardial injury (3). In their recently published elegant article (1), Lu et al (1) suggested plasma histone H4 as an important predictor of S-CMP evolution, along with vasopressor use, in a mixed population of sepsis and septic shock patients. Of note, the authors particularly focused on histone H4 both as a consequence and trigger of myocardial injury/dysfunction in the setting of S-CMP.…”
mentioning
confidence: 99%